Public Libraries and Walkable Neighborhoods - Lenstra, Noah (Int J Environ Res Public Health, 2019)
Public libraries constitute a ubiquitous social infrastructure found in nearly every community in the United States and Canada. The hypothesis of this study is that public libraries can be understood as important supports of walking in neighborhoods, not only as walkable destinations, but also as providers of programs that increase walking in communities. Recent work by public health scholars has analyzed how libraries contribute to community health. This particular topic has not previously been researched. As such, a qualitative, exploratory approach guides this study. Grounded theory techniques are used in a content analysis of a corpus of 94 online articles documenting this phenomenon. Results show that across North America public librarians endeavor to support walking through programs oriented around stories, books, and local history, as well as through walking groups and community partnerships. While this exploratory study has many limitations, it does set the stage for future, more rigorous research on the contributions public libraries and public librarians make to walking in neighborhoods. The principal conclusion of this study is that additional research is needed to comprehensively understand the intersection between public librarianship and public health.